PERTANGGUNGJAWABAN PIDANA MEDIA OT ATAS PEMBERITAAN TIDAK BENAR BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS - Katon Fajar Maulana; Ami Setyaningrum (Faculty of Law, University of Muhammadiyah Malang, 2018)
The purpose of this paper is to deeply understand criminal offense committed by the press for having announces that chief editor of the private television has caught by KPK hand fishing operation with the aim of making bombastic news, of course, the mass media in this case OT media will have a huge advantage over the news. The results showed that OT media in informing the US was caught in the KPK hand fishing Operation (KPK HFO) be accountable for their crime by the Press Law because; Based on the news that is not true, which stating that the US was caught KPK, the online media has violated Article 5 (1) of the Press Law, which determines that the national press is obliged to proclaim the events and opinions with respect religious norms and a sense of decency community as well as the presumption of innocence. In this case the media OT violates the presumption of innocence; Media OT does not carry out the role of the press as set forth in the provisions of Press law Article 6 letter C, which develop public opinion based on information that is precise, accurate, and true. Coverage improper done by media OT impressed incite people to cause controversy among the public; to determine Corporate criminal liability of the OT media is by using the theory of criminal liability Vicarious Liability, because the subject is corporate crime after the devolution of criminal liability of its officers, in this case the editor in chief in accordance with the explanation of Article 12 in conjunction with Article 18 of the Press Law. Based on the Fault made by the OT media, the online media can be penalized as provided for in Article 18 of the Press Law, which is subject to a maximum fine of Rp. 500,000,000.00.